Semito-Hamitic or Afro-Asiatic consonantism and lexicon: Episodes of a comparative research I (Part 1: The long century of Semito-Hamitology until the middle of the 20th century) - Takács, Gábor (Lingua Posnaniensis, 2023)
A retrospective account on past comparative research on Afro-Asiatic (AA) or Semito-Hamitic / Hamito-Semitic (SH/HS, resp.) phonology (first of all consonantism, also root structure) and lexicon, segmented into episodes according to diverse trends (often overlapping in time) is now under way and will be presented part by part in a series of papers. The present paper contains the first ever direction of this research, labelled “Semito-Hamitology” covering studies seeking, in their conception, the “African”, i.e. “Hamitic” kinship of Semitic, without a permanent communis opinio over the whole century of this ‘trend’ (better: amalgamate era) regarding the limits of the family.